KAJIAN MUSIKOLOGI MUSIK IRINGAN TARI JEPIN TEMBUNG KOTA PONTIANAK - Novianti, Novianti; Ismunandar, Ismunandar; Silaban, Christianly Yely (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract.The background of this research was to document Jepin Tembung dance accompaniment in Pontianak. The general problem contained in this resarch was: What is the description of Jepin Tembung dance accompaniment in Pontianak? The objectives o this research were: 1) Descriptions of Pontianak Jepin Tembung Dance accompaniment, 2) Descriptions of Poetry Melody in Pontianak Jepin Tembung Dance accompaniment, 3) Descriptions of Selodang Melody in Pontianak Jepin Tembung Dance accompaniment, 4) Descriptions of Marwas Rhythm Pattern in Pontianak Jepin Tembung Dance Accompaniment, 5) Descriptions of Implementation that will be used in teaching and learning activities in schools.Based on the data analysis, it can be concluded that Jepin Tembung Music accompaniment in Pontianak has a music component and foming characteristics and forms of modern music in general. The results of this study are in the form of accompaniment sheet music of Jepin Tembung Dance. There are poetic, selodang, marwas, violin, and accordion sheet music. This research is expected to stimulate the growth of interest in learning traditional music, especially Jepin traditional music, and more especially the accompaniment of Jepin Tembung Dance in Pontianak.Â Keywords: Jepin Music, Pontianak Jepin Tembung, Musicology